2017
DOI: 10.21512/bbr.v8i1.1958
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Entrepreneurship Education on Entrepreneurial Intention of University Students by Adopting Linan Model

Abstract: The success of entrepreneurship education programs remains unanswered if it is associated with some students who have decided to launch and pursue a business venture. It is important to know the intentions of a nascent entrepreneur to start up the business ventures persistently if experts and policy makers' attentions are drawn on how to arouse interest in starting a business. Quantitative approached was used in this research to examine the influence of entrepreneurship education, social norms and self-efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 62 publications
2
21
0
Order By: Relevance
“…The research results of Morris et al (2017) also show that there is a positive influence of involvement in curricular and co-curricular activities on the scope of start-up activities, with a low coefficient of influence. Some research results, for example, the results of research by Hussain and Norashidah (2015), Martyajuarlinda and Kusumajanto (2018), Periansya (2018), Praticia and Silangen (2016), Buana et al (2017), Mardisentosa et al (2018), and Sang and Lin (2019) showed a significant influence of entrepreneurship education on the interests and abilities of student entrepreneurs. The strong influence is quite apparent as entrepreneurship education was carried out specifically for the development of students' entrepreneurial abilities.…”
Section: Discussionmentioning
confidence: 99%
“…The research results of Morris et al (2017) also show that there is a positive influence of involvement in curricular and co-curricular activities on the scope of start-up activities, with a low coefficient of influence. Some research results, for example, the results of research by Hussain and Norashidah (2015), Martyajuarlinda and Kusumajanto (2018), Periansya (2018), Praticia and Silangen (2016), Buana et al (2017), Mardisentosa et al (2018), and Sang and Lin (2019) showed a significant influence of entrepreneurship education on the interests and abilities of student entrepreneurs. The strong influence is quite apparent as entrepreneurship education was carried out specifically for the development of students' entrepreneurial abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Second, entrepreneurial self‐efficacy and attitude towards entrepreneurship as two ways through which entrepreneurial education impacts students’ entrepreneurial intentions (Arshad et al., 2016; Buana et al., 2017; Shah et al., 2020). Our empirical findings support the notion that self‐efficacy plays a major role in the creation of entrepreneurial intention.…”
Section: Discussionmentioning
confidence: 99%
“…The entrepreneurship is vital for developing emotional strength of entrepreneurs to attain desired outcomes through application of various strategic approaches that are vital toward determination of desired outcomes based upon skills and knowledge through effective and vital application of the various strategic approaches (Buana, Hidayat, & Prayogi, 2017;Gabriela, Alina, Maria, & Daniel, 2020). The entrepreneurship is imperative for students to overwhelm the situation and to maintain desirability towards leading outcomes through effective education.…”
Section: Discussionmentioning
confidence: 99%
“…The entrepreneurship is imperative for students to overwhelm the situation and to maintain desirability towards leading outcomes through effective education. The entrepreneurial education, personality and intentions are effective in sustaining environment wherein entrepreneurs are required to put their strong efforts to avail the different available leading opportunities towards the application of different knowledge, techniques and approaches that are dynamic toward the determination of the required outcomes through effective and required capabilities and outcomes in the diverse situation to maintain anticipated consequences (Buana, Hidayat & Prayogi, 2017;Agustina, & Fauzia, 2021).…”
Section: Discussionmentioning
confidence: 99%